Marketing Mix Strategies to Increase Revenue of Le Vista Restaurant, Chamonix, France - Putu Zara Chandika Devi; Ni Nyoman Triyuni (International Journal of Glocal Tourism, 2021)
Purpose: This research aims to determine how is the implementation of the marketing mix strategies and to determine the right and effective marketing strategies to be implemented in increasing revenue of Le Vista Restaurant, Alpina Hotel & Chamonix, France. Research methods: This research was done at Le Vista Restaurant, Alpina Hotel & Spa Chamonix, France. Its data were collected through observation, interviews, documentation, and questionnaires. They were analyzed using SWOT analysis and QSPM analysis techniques. Findings: There are internal and external factors that influence marketing strategies in increasing revenue at Le Vista Restaurant, Alpina Hotel & Spa Chamonix, France. Based on the results of the IFAS analysis, the main strength is the easy access to go to Le Vista Restaurant from city centre or tourist destination in Chamonix area, while the main weakness is the service from staff to customers at Le Vista Restaurant. Based on the EFAS analysis, it is known that the main opportunity is the influence of customer expenditure pattern that affect the selection and purchase of products, while the main threat faced was local government regulations in the Covid-19 situation. Implications: The results of the IE put the company in the position of Growth Strategic (Cell II). SWOT analysis resulted in 8 strategies, obtained 3 priority marketing strategies and have been calculated through the QSPM with a total TAS of 332.76, 216.53, and 210.86 as follows prioritizing guest satisfaction by providing benefits such as providing satisfying service and affordable prices offered according to the experience gained, organizing special sales and marketing departments for Le Vista Restaurant, and adding product variants for restaurants such as creating packages for customers and innovating by creating different products according to the season in France.